Design of modern control systems - Bell, D. J. 1913- (David John); Cook, P. A. (Peter A.); Munro, N. (P. Peregrinus on behalf of the Institution of Electrical Engineers, 1982)
The book reviews developments in the following fields: state-space theory; complex variable methods in feedback system analysis and design; robustness in variable control system design; design study using the characteristic locus method; inverse Nyquist array design method; nuclear boiler control scheme analysis and design; optimal control; control system design via mathematical programming; multivariable design optimisation; pole assignment; nonlinear systems; DDC system design; robust controller design; distributed parameter system control; and decentralised control.